2017
DOI: 10.4314/wsa.v43i4.12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polychlorinated biphenyls in surface sediments of the North End Lake, Port Elizabeth, South Africa

Abstract: The distribution and concentrations of 6 indicator polychlorinated biphenyl (PCB) congeners, nos. 28, 52, 101, 138, 153 and 180, were determined in surface sediments from the North End Lake in Port Elizabeth, South Africa. Forty-two surficial sediment samples were collected from different locations covering the region that receives the majority of the industrial waste, urban effluents and runoff and thus expected to be contaminated with different degrees of contamination. The analysis was achieved by gas chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
7
2
Order By: Relevance
“…In other parts of Nigeria, PCBs levels in sediments from Choba River (0.1701 µgg -1 ) (Archibong et al, 2017), Ona River (589 -1353.6 µg/kg) and Ogun River (322.9-2002.6 µg/kg) (Adeogun et al, 2016) were much higher than those in the present study. In comparison to studies conducted in other African countries and countries outside Africa, levels of the PCB compound in sediments in the present study were lower than most of the levels reported by Kampire et al, (2017) Although the concentrations in sediments in the present study were relatively low, Obanya et al, (2018) asserted that chronic exposure to low concentrations of toxicants plays a greater role in toxicology than acute exposure. Surface Water: The results obtained from the lagoon surface water analysis indicated that 0.00133± 0.000667mg/L of 2,4,4'-TCB was detected in surface water from Zone 3 during the rainy season (Figure 3).…”
Section: Sedimentscontrasting
confidence: 92%
“…In other parts of Nigeria, PCBs levels in sediments from Choba River (0.1701 µgg -1 ) (Archibong et al, 2017), Ona River (589 -1353.6 µg/kg) and Ogun River (322.9-2002.6 µg/kg) (Adeogun et al, 2016) were much higher than those in the present study. In comparison to studies conducted in other African countries and countries outside Africa, levels of the PCB compound in sediments in the present study were lower than most of the levels reported by Kampire et al, (2017) Although the concentrations in sediments in the present study were relatively low, Obanya et al, (2018) asserted that chronic exposure to low concentrations of toxicants plays a greater role in toxicology than acute exposure. Surface Water: The results obtained from the lagoon surface water analysis indicated that 0.00133± 0.000667mg/L of 2,4,4'-TCB was detected in surface water from Zone 3 during the rainy season (Figure 3).…”
Section: Sedimentscontrasting
confidence: 92%
“…In this confined zone, the finer particles containing probably the PCBs (Perad 1996; Rybnikova 2016) react with the freeze-concentrated oxidant. Indeed, PCBs, that are hydrophobic compounds, are usually located on soil organic matter or silts and clays containing high extent of organic carbon, which account to the finest fraction of soil (Kampire 2017;Wilcke 1998). A second possibility is that upon freezing, pre-melted films are formed between the surfaces of soil grains and ice lens (Ji 2018;Peppin 2013;Xu 2018).…”
Section: Resultsmentioning
confidence: 99%
“…One gram of soil sample was thoroughly blended and homogenized with three grams of C18 using a glass mortar and pestle for 5 min [29]. One gram of anhydrous sodium sulfate (Na 2 SO 4 ), 1 g of Florisil, and 1 g of neutral silica gel were added to remove any trace of water and form a free-flowing powder [31] and then 1 g of activated copper powder was added to remove elemental sulfur [24,31]. The activated Na 2 SO 4 , Florisil, neutral silica gel, and copper powder were packed into a 10 mL syringe barrel column with 0.22 μm membrane filter from bottom to top.…”
Section: Methodsmentioning
confidence: 99%